2008
DOI: 10.1063/1.2831918
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic contact formation on n-type Ge

Abstract: Severe Fermi level pinning at the interface between n-Ge and a metal, leads to the formation of a Schottky barrier, almost independent on the metal work function. Therefore it seems impossible to form metal Ohmic contacts on moderately, n-type doped Ge layers. For p-type Ge the Fermi level pinning works opposite: all metal contacts show Ohmic behavior. This fixed behavior can be altered by the introduction of a thin Ge 3 N 4 layer. Ge 3 N 4 seems effective in reducing Fermi level pinning and therefore allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
116
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 9 publications
1
116
0
1
Order By: Relevance
“…45, the insertion of a thin GeO x layer between Ge and common metals led to substantial increases in the n-type junction current and reductions in the p-type junction current (inset). 325 This decrease (increase) in the n-type (p-type) SBH for Ge has also been observed for different metals and for a variety of insulating materials inserted as the interlayer, including amorphous and crystalline Ge 3 N 4 , 326,327 Si 3 N 4 , 311 AlO x , 312,325 MgO, 328 TaN, 314 and organic molecules. 297 The nominal SBH obtained from MIS stack typically showed a much stronger dependence on the metal work function than without the insulating interlayer, as shown in Fig.…”
Section: B Sbh Modification With Thin Layer Of Insulating Materialsmentioning
confidence: 98%
“…45, the insertion of a thin GeO x layer between Ge and common metals led to substantial increases in the n-type junction current and reductions in the p-type junction current (inset). 325 This decrease (increase) in the n-type (p-type) SBH for Ge has also been observed for different metals and for a variety of insulating materials inserted as the interlayer, including amorphous and crystalline Ge 3 N 4 , 326,327 Si 3 N 4 , 311 AlO x , 312,325 MgO, 328 TaN, 314 and organic molecules. 297 The nominal SBH obtained from MIS stack typically showed a much stronger dependence on the metal work function than without the insulating interlayer, as shown in Fig.…”
Section: B Sbh Modification With Thin Layer Of Insulating Materialsmentioning
confidence: 98%
“…Several approaches have been explored to overcome this problem. [13][14][15] Very recently, Yamane et al demonstrated a reduction in the Fermi level pinning even for metal/Ge contacts by using an atomically controlled interface between metal and Ge. 16 In this study, we combine high-concentration ␦-doping techniques with the formation of atomically controlled metal/Ge contacts.…”
mentioning
confidence: 98%
“…It is not enough to compare the work functions for Ge and metal in order to specify the type of the contact created between a Ge surface and a metal. The effect of the Fermi level pinning appearing in the interface between metal and n-type Ge causes the contact to be rectifying and rises the Schottky barrier the height of which is almost independent of the used metal work function [17,18]. On the other hand, due to the Fermi level pinning for p-type Ge, the contact of this semiconductor with metal show Ohmic behavior for all metals [17,18].…”
Section: Resultsmentioning
confidence: 99%